Bibliometric analysis of contemporary trends in cultural tourism - Danijela Pantović; Nevena Vasović; Ladislav Mura (Anali Ekonomskog fakulteta u Subotici, 2023)
Cultural tourism and the prospects it has are increasingly being talked about in academic circles. During the travels around the world, the terms cultural tourism and cultural heritage management have been constantly functioning in recent years. However, although experts in the field of cultural tourism and the tourism industry have multidimensional benefits in the management, preservation, and presentation of cultural assets, it is still not enough emphasized the multiple importance in this scientific field in terms of quantity of works. The purpose of this study is to form an adequate instrument for assessing current trends and future directions of cultural tourism research. Specifically, using bibliometric mapping, the study identifies changes in the conceptualization of cultural tourism perspectives. The results of the study will show leading journals in the field of dissemination of academic knowledge about cultural tourism, but also identify identified authors in this field.